Distribution of Water Infiltration Rate in Ciliwung Watershed - Pramono, Irfan Budi (Universitas Muhammadiyah Surakarta, 2016)
Floods in Jakarta showed that the Ciliwung watershed and surrounding areas in critical condition. More than 50 % of land cover Ciliwung watershed is residential. Planting trees in residential areas have been insufficient to infiltrate as much water into the ground. Infiltration well is one possibility for absorbing water in residential areas. The purpose of this study was to determine the variation in the level of water absorption Ciliwung watershed and surrounding areas. The method used is overlaying analysis of the factors that determine the rate of water infiltration with geographic information system. Each of these factors gave weights and scores to obtained variations Ciliwung water infiltration rate. The results showed that the regions with the highest levels found in the upper catchment area and the city of Bogor, middle absorbtion water area was in Bogor Regency, low water absorption areas in Depok , South Jakarta , and East Jakarta . While in North Jakarta, Central Jakarta and West Jakarta the water absortion is very low level due to the shallow ground water level and very low soil permeability. Map variations in water absorption can be used as a material consideration for determining the locations of recharge wells effectively.